Classical Hollywood cinema : Point of view and communication - Zborowski, James (Book collections on Project MUSE., 2016)
This text offers a new approach to filmic point of view by combining close analyses informed by the tools of narratology and philosophy with concepts derived from communication studies. It interrogates prevailing assumptions about film's ability to represent character experience and offers an alternative way of understanding and describing films' achievements in this regard.